FRIDAYS: A Financial Risk Information Detecting and Analyzing System - Du, Chi-Han; Chiang, Yi-Shyuan; Tsai, Kun-Che; Liu, Liang-Chih; Tsai, Ming-Feng; Wang, Chuan-Ju (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We present FRIDAYS, a financial risk information detecting and analyzing system that enables financial professionals to efficiently comprehend financial reports in terms of risk and domain-specific sentiment cues. Our system is designed to integrate multiple NLP models trained on financial reports but on different levels (i.e., word, multi-word, and sentence levels) and to illustrate the prediction results generated by the models. The system is available online at https://cfda.csie.org/FRIDAYS/.